Bilateral adrenal primary tumor in Stage 4S neuroblastoma: The Italian experience and review of the literature. (15th August 2022) - Montalto, Shana; Sertorio, Fiammetta; Podda, Marta; Sorrentino, Stefania; Di Cataldo, Andrea; Provenzi, Massimo; Nonnis, Antonella; D'Ippolito, Carmelita; Corrias, Maria Valeria; De Bernardi, Bruno
Abstract: Bilateral adrenal neuroblastoma (NB) is rare and is mainly stage 4S. Its incidence, presenting features, management, and outcome have not been fully defined yet. We searched the Italian NB Registry (RINB) for stage 4S NB infants with bilateral adrenal primary tumor to compare them with stage 4S NB with unilateral tumor. Between 1979 and 2016, the RINB enrolled 3731 NB patients aged 0-18 years including 317 infants (8.5%) diagnosed with stage 4S NB. Eleven/317 (3.5%) had a bilateral adrenal primary tumor (Group 1) and 190/317 (59.9%) had a unilateral tumor (Group 2). Group 1 infants were significantly younger (51 vs. 89 days) but were comparable with Group 2 for any other presenting features. In the absence of specific protocols, upfront treatment was based on symptoms, size of adrenal tumors, and biology, and consisted of observation in 5 cases, radiotherapy in one, chemotherapy in 2, and surgery in 3. Five/11 developed progression and 2 of them, both with MYCN amplification, died. The 5-year EFS rates of Group 1 and 2 were 54.5% vs. 73.3% (P=.14) and 5-year OSs were 81.8% and 89.4%, respectively (P=.44). Our data support the hypothesis that 4S NB infants with bilateral adrenal tumors can have favorable outcome with personalized therapeutic approach. The three patients with MYCN amplified tumor benefited from upfront aggressive chemotherapy, in accordance with current protocols. Because of the rarity of this intriguing form of neuroblastoma, collaborative prospective studies are warranted, especially in view of gaining a better insight on its biological and genetic features.